TECHNOLOGIES AND METHODS FOR MEASURING SOIL ACIDITY - KROPYVIANSKYI, YEVHENII; SAVITSKY, ANTON (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Soil acidity monitoring is a key aspect of modern agriculture, as pH levels significantly influence soil fertility, nutrient availability, and the overall health of ecosystems. Maintaining an optimal pH balance is essential for improving crop yields, ensuring efficient fertilizer absorption, and preventing soil degradation. Traditional laboratory methods for measuring soil acidity provide high accuracy but require considerable time and specific conditions, making them less suitable for real-time monitoring in large-scale agricultural applications. The growing need for automated and continuous soil monitoring has led to the development of various sensor-based technologies. This paper reviews modern methods for measuring soil pH, including traditional laboratory analysis, electrochemical sensors, optical sensors, nanotechnology-based approaches, and solid-state ISFET sensors. Each method’s working principles, structural design, and operational characteristics are analyzed and compared. While electrochemical and optical sensors offer faster measurements than laboratory methods, they are often influenced by environmental factors such as moisture content and temperature. Nanotechnology-based sensors provide extremely high sensitivity and precision but remain costly and require further research for large-scale agricultural implementation. A comparative calculation of the sensitivity of soil acidity measurement methods was performed, demonstrating that traditional laboratory methods achieve an accuracy of ±0.1 pH, while solid-state ISFET sensors offer improved accuracy at ±0.01 pH. The study highlights the advantages and limitations of each approach and justifies the selection of the ISFET-based sensor for further development. This choice is driven by its ability to deliver high accuracy, rapid response times, and seamless integration into wireless soil monitoring systems, making it an optimal solution for precision agriculture.